A facile and controllable, deep eutectic solvent aided strategy for the synthesis of graphene encapsulated metal phosphides for enhanced electrocatalytic overall water splitting. Issue 22 (22nd May 2019) - Mou, Hongyu; Wang, Jinfang; Yu, Dongkun; Zhang, Deliang; Lu, Fu; Chen, Lei; Wang, Debao; Mu, Tiancheng
Abstract : A facile, deep eutectic solvent aided strategy for the preparation of graphene encapsulated phosphides for enhanced electrocatalytic overall water splitting was proposed. Abstract : In this paper, we propose a new strategy to obtain graphene encapsulated Ni2 P via a simple annealing treatment of a designed deep eutectic solvent (DES). Ni2 P@graphene composite was taken as an example and prepared by applying the proposed strategy. The composition and structure of the encapsulated structures can be controlled by adjusting the component and molar ratio of the precursor DES. The obtained Ni2 P@graphene composite had excellent overall water splitting activity as an electrode, and a water splitting current of 10 mA cm −2 could be achieved by applying only 1.51 V. More importantly, the proposed strategy could be extrapolated for the preparation of other encapsulated structures.